Therapies used in the treatment of primary intestinal constipation (Research, Society and Development, 2023)
Intestinal constipation is a condition characterized by difficulty in defecating periodically and consistently, hard stools and the feeling that the rectum is not completely empty, which leads the patient to search for food and medication alternatives to reduce or stop symptoms. Constipation can occur in men and women differently, with women being the most affected. The objective of this work was to verify alternative treatments and prevention of intestinal constipation considering dietary and nutritional management as a means of preventing and treating functional constipation. The work involved a review of scientific articles from the last 10 years and theoretical books and sought references and information that brought together data on dietary management in the prevention and treatment of constipation to complement actions that implement dietary intervention proposals. The treatment of constipation must have an individualized approach, with specific treatment strategies, without disregarding the use of medications to control symptoms in isolation. Dietary adjustments with balanced diets are strategies that must accompany interventions and treatments to control constipation.